Conditioned medium as a strategy for human stem cells chondrogenic differentiation. (24th October 2013) - Alves da Silva, M. L.; Costa‐Pinto, A. R.; Martins, A.; Correlo, V. M.; Sol, P.; Bhattacharya, M.; Faria, S.; Reis, R. L.; Neves, Nuno M.
Abstract Paracrine signalling from chondrocytes has been reported to increase the synthesis and expression of cartilage extracellular matrix (ECM) by stem cells. The use of conditioned medium obtained from chondrocytes for stimulating stem cells chondrogenic differentiation may be a very interesting alternative for moving into the clinical application of these cells, as chondrocytes could be partially replaced by stem cells for this type of application. In the present study we aimed to achieve chondrogenic differentiation of two different sources of stem cells using conditioned medium, without adding growth factors. We tested both human bone marrow‐derived mesenchymal stem cells (hBSMCs) and human Wharton's jelly‐derived stem cells (hWJSCs). Conditioned medium obtained from a culture of human articular chondrocytes was used to feed the cells during the experiment. Cultures were performed in previously produced three‐dimensional (3D) scaffolds, composed of a blend of 50:50 chitosan:poly(butylene succinate). Both types of stem cells were able to undergo chondrogenic differentiation without the addition of growth factors. Cultures using hWJSCs showed significantly higher GAGs accumulation and expression of cartilage‐related genes (aggrecan, Sox9 and collagen type II) when compared to hBMSCs cultures. Conditioned medium obtained from articular chondrocytes induced the chondrogenic differentiation of MSCs and ECM formation. Obtained results showed that this new strategy is very interesting and should be further explored for clinical applications. Copyright © 2013 John Wiley & Sons, Ltd.